D-dimer as a Predictor of Altered Coagulation in HIV Patients in Nigeria (Nigerian Journal of Physiological Sciences, 2019)
Summary: Recent medical advances have improved the quality of life and correspondingly reduced the morbidity and mortality associated with HIV infection. However increased life expectancy has led to a relative rise in comorbidities and complications such as alterations in coagulation systems. This study is aimed at the evaluation of D-dimer level as a predictor of thromboembolic risk in HIV patients. A total of 152 HIV positive and negative subjects and control respectively attending the PEPFAR clinic UCH in Ibadan were recruited both for a questionnaire-based survey and a coagulation profile screening. Activated Partial Thromboplastin Time (APTT), Prothrombin Time (PT), D-dimer level the viral load indices of the HIV patients and their CD4 counts were also evaluated. In the subjects, the D-dimer level was significantly higher (193.6 ± 177.00ng/ml) than the controls (118.10 ± 140.58ng/ml) while a significantly lower APTT was also reported (36.22 ± 4.05 seconds) compared to the controls (41.14 ± 8.87 seconds). An evaluation of the coagulation profile in the Highly Active Antiretroviral Therapy (HAART) naive and experienced group revealed only a significant difference (417.4 ± 162.0 versus 268.2 ± 193.5; p value 0.000) in the CD4 counts whilst no significant changes in the coagulation profile. In our study, a higher predisposition to a hypercoagulable state presenting as a short APTT was observed. This finding along with the higher D-dimer level underscores the relevance of the evaluation of this biomarker as an important predictor of thromboembolic event risk.
Keywords: HIV; thrombotic event; D-dimer; altered coagulation profile; CD4 count; APTT; PT